Investigation and evaluation of speed table influence on road traffic induced Ground borne vibration - Astrauskas, Tomas; Grubliauskas, Raimondas; Januševičius, Tomas (International Conference “Environmental Engineering”, 2017)
Vertical Speed Control Measures are vertical elevated segments of roadway that require a vehicle to slow. Typical vertical speed control measures include speed humps, speed tables, raised sidewalks and raised intersections. These engineering measures are used to reduce risk to pedestrians of crossing streets where transport flow is big. The object of this research is speed table. Measurements of ground borne vibration was done 1 m near the speed table and in reference point, in the same street where the speed table do not influence the traffic speed. Reference measurement point is in the same distance to the street as to the speed table. Measurements was done in two seasons: cold and warm. Ground borne vibration measurements took place in L. Asanavičiūtės st., Vilnius. In this research was found that highest acceleration value near the speed table was 21,8 mm/s2 when heavy weight vehicles was passing, in reference point highest value was 38,1 mm/s2. Heavy weight vehicles induce highest ground borne vibration peaks.
Keywords: Speed table; Ground borne vibration; traffic calming; traffic induced vibration